Basis Properties of Eigenfunctions of Second-Order Differential Operators with Involution - Asylzat Kopzhassarova; Abdizhakhan Sarsenbi (Abstract and Applied Analysis)
We study the basis properties of systems of eigenfunctions and associated functions for one kind of generalized spectral problems for a second-order ordinary differential operator.